Multipolarity and the Future of Regionalism: Latin America and Beyond - Jorge F. Garzón (German Institute of Global and Area Studies (GIGA), 2015)
This paper inquires into the effects of an emerging multipolar world on the international institution of regionalism. While IR scholarship has been making a strong case for the regionalization of world politics since the 1990s, the fact that most of the rising powers are also the sole regional powers of their home regions has led some scholars to argue that the advent of multipolarity can only strengthen this general trend toward a more regionalized international order. In this contribution, I challenge these arguments by proposing an alternative way of thinking about how multipolarity is developing. The implications of this interpretation are that the emergence of multipolarity may actually generate powerful centrifugal forces within regions, which would have adverse effects on the known forms of regionalism that regional groupings have been implementing thus far. This applies particularly to the global South, where intraregional economic interdependencies tend to be weak. The proposition is tested by examining empirical findings across several regions and through a case study.
Keywords: 300; multipolarity; regional powers; regionalism; regional integration; open regionalism